Are vaccine shortages a relevant public health issue in Europe?. (30th September 2020) - Filia, A; Rota, M C; Grossi, A; Martinelli, D; De Graaf, T; Dominguez, A; Tuells, J; Sormunen, P; Jønsrud, K; Rezza, G
Abstract: Background: National immunisation programmes depend on an adequate supply of vaccines but shortages have become more frequent globally in recent years. Vaccine shortages can lead to missed opportunities for vaccination and a greater risk of occurrence of vaccine-preventable diseases (VPD). Methods: The EU-Joint Action on Vaccination is a European Commission-funded project* which aims to strengthen cooperation between European countries against VPDs, including improvement of vaccine supply and preparedness. In this context, from February to May 2019, we conducted a survey amongst persons in charge of national immunisation programmes or of vaccine supply/procurement in EU/EEA, to collect information on vaccine shortages in the previous three years. Results: Twenty-one of 28 invited countries responded, of which 19 reported at least one shortage, for a total of 115 shortage events. The median number of shortages per country was 5 (range 0-15). At the time of survey completion, there were ongoing shortages in six countries. DT/dt-containing combination vaccines, hepatitis A, hepatitis B and BCG vaccines were the most frequently involved vaccines. Supply and production issues, and global shortage, were the most frequent causes. Median duration of shortages was five months; 34% caused a disruption in immunization services. Procurement and purchase methods varied by country. Only half of countries have recommendations or procedures in place to address shortages. Conclusions: Vaccine shortages are a serious public health issue in the EU. Causes are complex and multifaceted and more research is needed to understand the economic and market-related causes. Improved communication between public health authorities, manufacturers and regulatory agencies is essential. Procurement and tender mechanisms should be improved. In case of vaccine shortages, all countries should have procedures or recommendation in place regarding the use of alternative vaccines or vaccination schedules. Key messages: Vaccine shortages are a relevant public health issue in the EU. More research is needed on the complex and multifaceted causes of vaccine shortages. Timely communication between supply and demand is needed and procurement and tender mechanisms should be improved.